PERBEDAAN KEPUASAN HIDUP LANJUT USIA YANG TINGGAL BERSAMA KELUARGA DAN YANG TINGGAL DI PANTI WERDHA - Aseng, Krisna Gita; Bidjuni, Hendro; Rompas, Sefti (JURNAL KEPERAWATAN, 2025)
Background: Elderly life satisfaction is influenced by family support and the environment in which they live. The opportunity of elderly who living in nurshing home to interact with their families has been reduced compared to the elderly who still live with their families so that it can cause feelings of loneliness and dissatisfaction in their lives. Aim: to determine differences in the life satisfaction of elderly who live with family in Wiau-Lapi village Tareran district and who living in nursing home Senja Cerah Manado. Methods: this research design used observational analytics, with a crosssectional approach. The sample amounted to 60 respondents, namely 30 respondents in Wiau-Lapi Village Tareran district 30 and 30 respondents in nursing home Senja Cerah Manado obtained by using purposive sampling technique. Result: The research results of statistical tests using Mann Whitney test at the 95% significance level, obtained a significant value of Ï = 0.000< Î± (0.05). Conclusion: The life satisfaction of the elderly living with family is higher compared to the life satisfaction of the elderly in the nursing home. This research can be a reference for planning and evaluation of improvement programs in the field of nursing for the improvement of the psychosocial needs of the elderly who living with family and in nursing home.Keywords : elderly; life satisfaction